Podatkowy kontekst długu sektora general government - Ziółkowska, Wiesława (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The purpose of the paper is to present a retrospective analysis of taxation in thecontext of public debt in the years 1995–2013. The author attempts to verify thehypothesis according to which there is correlation of various degrees of significanceand various directions between taxes and the debt of the general government sectorof the EU Member States. The study of those correlations was preceded by ananalysis that indicated tendencies to diminish tax burdens which was a result of„copying” tax policy and simultaneously increase sources and change character ofthe causes of increasing public debt. Out of 25 states where the correlation betweentwo major groups of taxes in GDP and public debt was proved, in 15 states thedimension of the interdependence was positive, while in the remaining 10 – negative.In the first group the lower (higher) tax burdens were, the lower (higher) thepublic debt was. Therefore it might be inferred that the tax rate below or abovewhich the budget income moves was not exceeded. As far as the remaining 10countries are concerned (those with negative correlation), it might be suggestedthat the critical point of decreasing (increasing) taxes below (above) which theincome drops was exceeded. Both the descriptive analysis of the indices and statisticalexamination make it possible to verify the adopted hypothesis positively,indicating simultaneously the necessity for further examination.